Cultivating the Caregivers: How Employee Well-being Programs in Livestock Farms Drive Operational Success - Dwi Savandha, Septien (Livestock Science & Innovation Journal, 2024)
Employee well-being is increasingly recognized as a key driver of operational success in labor-intensive industries, particularly in livestock farming. Workers in this sector endure physically demanding tasks, long working hours, harsh environmental conditions, and high-stress levels, all of which can negatively affect productivity, job satisfaction, and workplace safety. This study investigates the impact of well-being programs on employee productivity, retention, health, and overall farm performance, focusing on livestock farms in West Java, Indonesia. Using a qualitative descriptive approach, the research involves semi-structured interviews and field observations with farmworkers and managers. The study evaluates the effectiveness of well-being initiatives, including mental health support, physical wellness programs, and safety training. Findings reveal that farms implementing comprehensive well-being programs experienced a 50% reduction in workplace injuries, a 40% decrease in health-related absenteeism, and a 30% improvement in employee retention. Additionally, task completion rates increased by 25%, and overall worker engagement improved by 35%. The results underscore the strategic benefits of investing in employee well-being for improved operational efficiency and sustainability in livestock farming. From a policy perspective, these findings highlight the need for regulatory support and incentives to encourage farms to implement structured well-being programs. Policymakers should consider integrating mandatory health and safety training, financial incentives for wellness initiatives, and industry-wide standards for employee welfare. This study provides valuable insights for farm owners, policymakers, and researchers, reinforcing the critical role of employee well-being programs in ensuring long-term agricultural success.